Effect of X-ray spectrum on size-specific dose estimates (SSDEs) for paediatric and adult patients undergoing CT scans. (February 2021) - Abuhaimed, Abdullah; Martin, Colin J.
Abstract: The size-specific dose estimate (SSDE) concept is based on converting volume averaged CT dose index (CTDIvol ) measured in cylindrical PMMA head and body phantoms of reference sizes to values for doses absorbed in individual patients. The original conversion factors used for SSDE is related to the effective diameter (ED) of the region of interest for the patient. ED is simple to measure, but does not include attenuation, which affects estimation of the dose absorbed. Water-equivalent diameter (Dw ) which takes account of attenuation through the CT number, based on the linear attenuation coefficients, has been recommended to replace ED. The main scan parameter that affects Dw values is the x-ray spectrum. In this study, a library of 363 phantoms (168 paediatric and 195 adult) of a wide range of sizes from newborn to large adult were used to investigate the influence of the x-ray spectrum on Dw and the correlation between ED and Dw . Values were assessed for each phantom over seven scanned regions: head, chest, abdomen, pelvis, chest-abdomen, abdomen-pelvis, and the whole trunk using x-ray spectra of 80–140 kVp. The results show the effect of x-ray spectrum on the relationship between Dw and ED for the trunk regions was minimal, and almost all Dw /ED ratios were within a factor of ±1.01. However, Dw /ED values for the head region varied by a factor of up to 1.10 with the x-ray spectra. Energy-independent correlations between ED and Dw values for the trunk regions have been established. The correlations were compared with published results calculated by AAPM using another method and gave an average difference of 2.9%. Use of the correlations should simplify determination of the SSDE taking account of attenuation based on ED that is more readily measurable than Dw, which requires advanced software. Highlights: The influence of CT x-ray spectrum on patient size for SSDE has been investigated. Water-equivalent diameter (Dw ) is recommended for evaluating patient size for SSDE. The effect of spectrum was minimal for the trunk, but was significant for the head. Energy-independent correlations have been established to simply assessment of Dw .